2001
DOI: 10.1093/jac/48.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Airways delivery of rifampicin microparticles for the treatment of tuberculosis

Abstract: A Mycobacterium tuberculosis (H37Rv)-infected guinea pig model was used to screen for targeted delivery to the lungs by insufflation (with lactose excipient) or nebulization, of either rifampicin alone, rifampicin within poly(lactide-co-glycolide) microspheres (R-PLGA) or polymer microparticles alone (PLGA). Animals treated with single and double doses of R-PLGA microspheres exhibited significantly reduced numbers of viable bacteria, inflammation and lung damage compared with lactose-, PLGA- or rifampicin-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(57 citation statements)
references
References 6 publications
2
54
0
1
Order By: Relevance
“…Delivery of the microspheres to the lower airways would most likely be achieved by nebulization. Nebulization of pharmacological agents encapsulated in PLG has been described, particularly for airway delivery of antituberculous therapy, 23 but the effect of nebulization on PLG-encapsulated plasmid DNA has not yet been studied. While encapsulation of the DNA potentially offers a way to both protect DNA from degradation 15 and also control its release, 7 analysis of DNA extracted from our microspheres, as well as in previous studies, 6 revealed a relative increase in the amount of nicked DNA compared to supercoiled.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of the microspheres to the lower airways would most likely be achieved by nebulization. Nebulization of pharmacological agents encapsulated in PLG has been described, particularly for airway delivery of antituberculous therapy, 23 but the effect of nebulization on PLG-encapsulated plasmid DNA has not yet been studied. While encapsulation of the DNA potentially offers a way to both protect DNA from degradation 15 and also control its release, 7 analysis of DNA extracted from our microspheres, as well as in previous studies, 6 revealed a relative increase in the amount of nicked DNA compared to supercoiled.…”
Section: Discussionmentioning
confidence: 99%
“…These studies measured the decrease in glucose levels after administration of insulin formulations. The reduction of bacterial burden in affected organs after aerosol administration has also been used to assess the pulmonary disposition of anti-tubercular drugs [96,97,91,111].…”
Section: Methods To Calculate the Rate Of Absorption And Pulmonary Bimentioning
confidence: 99%
“…Solution and suspension aerosols have been characterized and shown to retain the median particle size and distribution generated by the nebulizer after passing through the chamber [96,97]. Presumably this can be attributed to the relatively small volume of the chamber and reduced tendency to lose particles by impaction and sedimentation [82].…”
Section: Passive Inhalationmentioning
confidence: 99%
“…Approximately 1 mg of either TMA (Aldrich Chemical Co.; 97% purity) or lactose (Sigma Chemical Co.) was insufflated into the airways, via the tracheal cannula, just distal to the carina. TMA and lactose were administered as a bolus using a dry powder delivery device (DP-3 Insufflator, PennCentury, Philadelphia, PA; see Concessio et al, 1999;Suarez et al, 2001 for examples of previous use in the guinea pig). The dose delivered was determined by the difference in weight between the loaded delivery device and the weight of the device after insufflation.…”
Section: Methodsmentioning
confidence: 99%